> 30 W vortex LG or HG laser using a modetransforming output coupler - Geberbauer,J; Kerridge-Johns,W; Damzen,M (Optics Express, 2021)
High-power vortex light generated directly from lasers will help drive theirapplications in material processing, optical manipulation, levitation, particle acceleration, andcommunications, but limited power has been achieved to date. In this work, we demonstraterecord vortex average power of 31.3 W directly from a laser, to the best of our knowledge,using an interferometric mode transforming output coupler to convert a fundamental modeNd:YVO4 laser into a LG01 vortex output. The vortex laser was Q-switched with up to 600 kHzpulse rate with a high slope efficiency of 62.5% and an excellent LG01 modal purity of 95.2%.We further demonstrate > 30W laser power in a high quality HG10 mode by simple adjustmentof the output coupler. Experimental investigations of varying output coupling transmission arecompared with theory. This successful implementation of the interferometric output coupler ina high power system demonstrates the suitability of the mode transforming method for robustturn-key vortex lasers with high efficiency and high modal purity, with scalable power andpulse rate.